ECONOMETRIC SCALES OF EQUIVALENCE, THEIR IMPLEMENTATIONS IN ALBANIA - Xhafaj, Evgjeni; Nurja, Ines; Xhafaj, Alban (European Scientific Journal, ESJ, 2014)
Econometric scales are, by one consent, considered a necessary tool in poverty analysis, welfare comparison and income distribution analysis. The calculation of equivalence scales based on a food ratio applied as a welfare measure is well known as the Engel’s method. In this paper, the aim is to calculate the econometric scales based on a food ratio applied as a welfare measure; parametric regression is used for the estimation of the Engel curves. The Engel method is based on the observation that, for any given household composition, the share of food expenditures on total expenditures is inversely related to income. That is to say, two household with different number of members but that have the same food expenditure achieve the same level of welfare even if they have different incomes (major to the larger household). The method is applied to the data set of Household Budget Survey in Albania in 2008. The economic resources to achieve a given level of welfare are not directly proportional to the household size. The poverty line is estimated using the method of expenditure of consumption mediana. As the same methodology is applied two times, introducing as single element of diversification in the analytical process, two different equivalent scales, the final result can be considered a sort of a ‘analysis of sensibility’.